2020
DOI: 10.3847/1538-4357/aba6e9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Energy Sources Powering the Light Curve of the Type Ibn Supernova PS15dpn and the Mass-loss History of the SN Progenitor

Abstract: PS15dpn is a luminous rapidly rising Type Ibn supernova (SN) discovered by Pan-STARRS1. Previous study has showed that its bolometric light curve (LC) cannot be explained by the 56Ni model. In this paper, we used the 56Ni model, the magnetar model, the circumstellar interaction (CSI) model, and the CSI plus 56Ni model to fit the bolometric LC of PS15dpn. We found that the 56Ni model can fit the bolometric LC but the parameters are unrealistic, and that the magnetar model, the CSI model, and the CSI plus 56Ni m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The ejecta drives a shock through the CSM, which converts the ejecta kinetic energy into thermal energy, leading to the bright event observed. The model has been applied to recent superluminous SNe such as SN 2008gy (Woosley et al 2007), SN 2007bi, SN 2010gx and PTF 09cnd (Sorokina et al 2016), iPTF 14hls (Woosley 2018), PTF 12dam (Tolstov et al 2017), SN 2016iet (Lunnan et al 2018), iPTF 16eh (Gomez et al 2019), AT 2018cow (Leung et al 2020b), and PS 15dpn (Wang & Li 2020).…”
Section: Circumstellar Medium Interaction Mechanismmentioning
confidence: 99%
“…The ejecta drives a shock through the CSM, which converts the ejecta kinetic energy into thermal energy, leading to the bright event observed. The model has been applied to recent superluminous SNe such as SN 2008gy (Woosley et al 2007), SN 2007bi, SN 2010gx and PTF 09cnd (Sorokina et al 2016), iPTF 14hls (Woosley 2018), PTF 12dam (Tolstov et al 2017), SN 2016iet (Lunnan et al 2018), iPTF 16eh (Gomez et al 2019), AT 2018cow (Leung et al 2020b), and PS 15dpn (Wang & Li 2020).…”
Section: Circumstellar Medium Interaction Mechanismmentioning
confidence: 99%
“…In SNe Ibn, the combination of narrow emission lines seen in spectra at early times and the fast rise to peak luminosity point to CSM interaction as a primary power source. Modeling the light curves of SNe Ibn has shown that either a combination of CSM interaction and 56 Ni decay (Clark et al 2020;Wang & Li 2020;Wang et al 2021) or CSM interaction alone (Karamehmetoglu et al 2019) can sufficiently reproduce their luminosity evolution.…”
Section: Model Descriptionmentioning
confidence: 99%
“…All of our models require a significant CSM mass relatively close to the progenitor star, indicating a large rate of mass loss shortly before explosion. An increase in mass loss rates may be common in the years prior to interaction-driven SNe (Ofek et al 2014;Bruch et al 2021;Strotjohann et al 2021), including eruptive mass loss events (Wang & Li 2020). A proposed progenitor of SNe Ibn are WR stars (Foley et al 2007;Smith et al 2012), yet they have not been observed to undergo violent luminous blue variable-like eruptions.…”
Section: Common Progenitor Scenariosmentioning
confidence: 99%
“…The LC of the type Ia supernova 2018oh has an unusual two-component shape [1], the radio LC of SN 1998bw shows a double-peak profile, possibly associated with density variations in the circumstellar medium [2], the R-band LCs of 265 SNs from the Palomar Transient Factory are followed and a model-independent LC template is built from this data-set [3], SN 2007D (which is a luminous type Ic supernova) has a narrow LC and high peak luminosity that were explored with a multi-band model [4]. Evolutionary models for the LC were introduced using the STELLA software application [5], the conversion of the kinetic energy of ejecta to radiation at the reverse and forward shocks was introduced in [6], the LC was modeled in the framework of the radioactive decay of 56 Co, 57 Co and 55 Fe [7], the cosmological importance of the LC was analysed by [8], and PS15dpn was a luminous rapidly rising Type Ibn SN which was modeled in the framework of the circumstellar interaction (CSI) model plus 56 Ni decay [9]. The previous papers leave a series of questions unanswered.…”
Section: Introductionmentioning
confidence: 99%